An Experimental Study on Behavior of Sustainable Rubberized Concrete Mixes - Kadhim, Ali Abdulameer; Al-Mutairee, Hayder M. K. (Salehan Institute of Higher Education, 2020)
In terms of recycling and reuse, today's global generation of waste tire well exceeds its consumption. This has resulted in the accumulation of large stocks of toxic rubber waste that raise health and safety risks. The use of waste tire rubber for the construction of the concrete structure was suggested to combat this challenge. This paper explores tests that were performed with samples of waste tire rubber concrete to evaluate compressive strength, flexural tensile strength, modulus of rupture, and impacts resistance. The main parameters investigated were the rubber ratio as a partial volumetric replacement with fine and coarse aggregate. Chip and crumb rubbers were used to replace coarse and fine aggregate respectively in four different amounts by volume (5%, 10%, 15%, and 20%). Even if the inclusion of waste tire rubber in concrete has specific apparent degradations, the potential benefit seems to overlook the adverse effects and also meet the primary significant value of resolution for rubber waste utilization problems. The results show that the substitution of natural fine or coarse aggregates with crump-chip tier rubber will reduce mechanical properties (compressive, flexural and splitting tensile strength), but increase the impacts resistance to 426% and 396% when 20% coarse aggregates and 20% fine aggregates are replaced by rubber respectively. The proposed mix shows an ability to replace 20% of the aggregate (coarse or fine), and the producing, rubcrete, still structural concrete.